Lipid metabolism in adipocytes modulates tumor growth at a distance through Nplp2-mediated Wnt5 signal. - Yang, C.; Yang, Y.; Liu, Z.; Bai, X.; Ma, X.; Tang, J.; Huang, R.; Liao, Y.; Liu, Y.; Wen, L.; Liu, M.; Zhu, A.J.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2026)
The host metabolic state can potentially affect the growth trajectories of tumors growing at local sites, which are highly variable and unpredictable among populations. The molecular links between systemic metabolism and tumor growth outcomes remain largely unclear. Here, we harnessed the genetic power of the Drosophila model to perform genetic screens and identified molecular players in the adipose tissue that can change the growth trajectory of remotely growing tumors. We found that variation of triacylglycerol (TAG) metabolism state in adipocytes, which is downstream of insulin signaling regulation, can strongly change the growth trajectory of distant tumors. Mechanistically, we identified that Wnt5, which is secreted from adipocytes and transported in circulation through a population of Nplp2-lipoprotein particles, is required for distant tumor growth. Perturbation of TAG metabolism or depletion of Nplp2-lipoprotein particle formation in adipocytes reduces Wnt5 in circulation and therefore restricts distant tumor growth.